Lewisville School. - (:unkn) unknown (Forsyth County Public Library, 2010)
Undetermined date.
Lewisville School. The school operated from 1923 to 1945.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth